2016
DOI: 10.1055/s-0042-105641
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose and Lipopolysaccharide Activate NOD1- RICK-NF-κB Inflammatory Signaling in Mesangial Cells

Abstract: Systemic and local low-grade inflammation and release of proinflammatory cytokines are implicated in the development and progression of diabetes mellitus (DM) and diabetic nephropathy (DN). The TLR2, TLR4, and NLRP3 inflammasomes of the innate immune system produce various proinflammatory cytokines and are critically involved in inflammatory responses in kidney tissues. The NOD-like receptor (NLR) NOD1 is involved in the NF-κB inflammatory signaling pathway and has an important role in the development of insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Our results showed that TLR2 activation leads to an increment in NOD1 expression (mRNA and protein) in Caco‐2/TC7 cells, and supporting this interdependence, NOD1 activation produced a decrement in TLR2 expression. Regarding TLR4, several authors have shown a synergic response with NOD1 (Huang et al, ), which agree with our data where TLR4 activation by LPS decreased significantly NOD1 expression in Caco‐2/TC7 cells. Furthermore, in the ileum of tlr4 −/− mice, NOD1 expression increased, which corroborates the fact that TLR4 activation could downregulate NOD1 mRNA and protein expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that TLR2 activation leads to an increment in NOD1 expression (mRNA and protein) in Caco‐2/TC7 cells, and supporting this interdependence, NOD1 activation produced a decrement in TLR2 expression. Regarding TLR4, several authors have shown a synergic response with NOD1 (Huang et al, ), which agree with our data where TLR4 activation by LPS decreased significantly NOD1 expression in Caco‐2/TC7 cells. Furthermore, in the ileum of tlr4 −/− mice, NOD1 expression increased, which corroborates the fact that TLR4 activation could downregulate NOD1 mRNA and protein expression.…”
Section: Discussionsupporting
confidence: 93%
“…TLR4 is expressed, as TLR2, in the cell surface and recognizes LPS from Gram‐negative bacteria. NOD1, able to detect DAP present in all bacteria membrane, could also recognize LPS, resulting in a collaborative response with TLR4 (Huang et al, ). Moreover, TLR4 activation seems to inhibit ERK/MAPK downstream kinase, which is the intracellular pathway involved in NOD1's effect on SERT (Shinohara et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation are inseparably linked as each causes and intensifies the other, which could cause glomerulosclerosis, tubular atrophy, and fibrosis [21]. Our previous research showed high glucose and LPS prime the NLRP3 inflammasome and NF-κB inflammatory signaling in GMCs via ROS/TXNIP pathway [22]. Up to present, several studies have looked into the effect of stress and inflammatory signaling pathways as effector mechanisms of SCFAs, the anti-inflammatory activity of SCFAs or GPR43 agonist were shown to inhibit the production of ROS and oxidative stress in this and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the GO enrichment analysis results, the potential targets of shenzhuo formula acting on DN were mainly associated with various biological processes, such as lipopolysaccharide-mediated signaling pathway, inflammatory response, positive regulation of cyclase activity, protein kinase B signaling, positive regulation of MAP kinase activity, response to estradiol, which have a strongly direct correlation with the pathogenesis of DN [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 94%